ESTABILIDADE E FOTOPROTEÇÃO DE FORMULAÇÕES CONTENDO EXTRATO DE PUNICA GRANATUM E METOXINAMATO DE OCTILA: STABILITY AND PHOTOPROTECTION OF FORMULATIONS CONTAINING EXTRACT OF PUNICA GRANATUM AND OCTIL METOXINAMATE (Revista Contexto & Saúde, 2022)
Ultraviolet radiation causes cumulative and irreversible skin aggressions and photoprotection remains the most effective way to prevent skin cancer and photoaging. Many beneficial effects attributed to medicinal plants and their bioactive compounds have been the subject of studies. Objective: to develop cosmetic formulations containing the commercial extract of P. granatum, added or not with synthetic organic sunscreen and evaluate the stability and the Sun Protection Factor. Method: the formulations were developed containing 1, 3 and 10 % of the extract of P. granatum, with or without 7 % of octyl methoxinamate, in non-ionic cream, and its physical-chemical stability was evaluated, by determining the organoleptic characteristics, pH and viscosity. Spreadability and SPF in vito were also evaluated. Results: the formulations containing only the extract of P. granatum showed the greatest variations in the stability study and octyl methoxinamate seems to interfere with stability. Conclusion: it is concluded that the formulation containing 10 % of  P. granatum extract and 7 % of octyl methoxinamate presented, in addition to adequate stability, an increase in SPF, which would provide a reduction of organic sunscreens in photoprotective formulations. It is recommended that this formulation be kept at room temperature and protected from light, heat and humidity.